COVERAGE WITH TESTS AND FREQUENCY OF MULTIPLE/EXTENSIVE DRUG RESISTANT TUBERCULOSIS IN THE CIVILIAN HEALTH SERVICES AND PENITENTIARY SYSTEM - V. V. Testov; S. A. Sterlikov; I. A. Vasilieva; Yu. V. Tikhonova; K. A. Glebov; A. E. Panova (Туберкулез и болезни лёгких, 2019)
.